Agrophysiological constarints in intercropped cowpea: an analysis - Terao, T.; Watanabe, I.; Matsunaga, R.; Hakoyama, S.; Singh, B. (1997)
Factors affecting cowpea growth in millet/cowpea intercropping were investigated in northern Nigeria. Ecological studies showed that cowpea received from < 30% to > 75% of incident light inside the intercropped canopy. In these light-limited conditions, cowpea varieties with a spreading growth habit can harvest more light than those with an erect growth habit by producing more leaves, as well as expanding their leaf area. However, the local spreading type has a low yield potential because of its low harvest index and inadequate root system (compared to the shoot system). Improvement of these two points in the local spreading variety without reducing its adaptability to shade ill produce a variety that is better adapted to intercropping. The effect of shade is most serious in the branch initiation stage, about 3—4 weeks after sowing, which inhibits branching significantly. Since leaves, which become source, as Well as pods, which become sink, grow on each branch and the main stem, the final grain yield in non branched cowpea is significantly reduced. Shade in the grain-filling stage also reduces final seed yield, but the effect is not as pronounced as shading during the branch-initiation stage. Root competition between cowpea and millet was greatest when cowpea was planted simultaneously with millet in the low rainfall environment. In alternate row intercropping With 75 cm row width, millet roots run horizontally and turn deep under the cowpea plants, while cowpea roots are distributed under the cowpea plant itself. This creates high root competition because roots of both species share the same root zone. In these conditions, if cowpea is planted simultaneously, millet roots are reduced in the deep zone. Consequently, early onset of drought reduces millet yield because millet does not have deep roots if planted simultaneously with cowpea.